Gulzar’s Films: Alice in Bollywood - Haq, Basharat Ul (International Journal For Research In Educational Studies, 2016)
This paper examines Gulzar in light of films directed by him. Gulzar is rare among the rarest who possesses multidimensional qualities. Whatever he tried his hand in he succeeded. Gulzar as a director has his own unique identity. In directing films there is a disciplined mechanism. His films depict peak of his genius. His films are not mere entertainment. They are laced with diverse messages so that one can translate them in one’s life. They are brightened by different colours of life. They have unity and pattern. All these elements give him a unique identity. It would not be wrong to say that Gulzar directed films with diverse themes which demonstrate his hold on his art. Gulzar directed seventeen films from Mere Apne to Hu Tu Tu.